Designing a Hybrid Multidimensional Curriculum for Arabic Learning in Islamic Boarding Schools - Moh Nadhif; Siti Imaniatul Muflihatin; A. Samsul Ma'arif; Rifqi Abqoriya (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2026)
This study aims to develop and validate a hybrid multidimensional curriculum model for Arabic language learning in Islamic boarding schools. The study addresses the gap between traditional grammar-based instruction and contemporary communicative approaches in non-formal Islamic education. Using a design-based research (DBR) methodology, the researchers conducted the study in an Arabic language center in Indonesia. The research involved iterative phases of needs analysis, curriculum design, expert validation, field implementation, and evaluation. The findings indicate that the proposed model integrates grammar-based, communicative, situational, and skill-based approaches, resulting in improved learner engagement and language competence. This study contributes to Arabic language pedagogy by offering a context-sensitive and theoretically grounded curriculum model applicable to similar educational settings.